Comparison of early vascular morphological changes between bioresorbable poly-L-lactic acid scaffolds and metallic stents in porcine iliac arteries. (3rd April 2017) - Sekimoto, Yasuhito; Obara, Hideaki; Matsubara, Kentaro; Fujimura, Naoki; Harada, Hirohisa; Kitagawa, Yuko
ABSTRACT: Bioresorbable scaffolds have the potential to overcome several problems associated with metallic stents. Bioresorbable poly-L-lactic acid (PLLA) scaffold implantation for the treatment of peripheral artery disease has already been reported in animal models and clinical trials; however, no studies comparing PLLA scaffolds and bare metal stents (BMSs) with regard to early vascular morphological changes, identified using intravascular ultrasound (IVUS) analysis, have been reported. In this study, PLLA scaffolds and BMSs were implanted bilaterally in iliac arteries of five miniature pigs. Digital subtraction angiography and IVUS were performed before and immediately after stent implantation and at 6-week follow-up. All PLLA scaffolds and BMSs were patent at 6-week follow-up. Per IVUS analysis, the percent area stenosis did not significantly differ between PLLA scaffolds and BMSs (65.7% vs. 67.2%, P = .761). Furthermore, percent vessel lumen change also did not differ significantly. Neointima formation (the neointimal area plus medial area) was significantly less with PLLA scaffolds than with BMSs (15.65 mm 2 vs. 25.69 mm 2, P < .001). In conclusion, based on IVUS results, short-term results after stent implantation in porcine iliac arteries were comparable between PLLA scaffolds and BMSs. Therefore, PLLA scaffolds are safe and feasible for implantation in peripheral arteries.